2018
DOI: 10.3390/ph11040124
|View full text |Cite
|
Sign up to set email alerts
|

Emerging and Dynamic Biomedical Uses of Ferritin

Abstract: Ferritin, a ubiquitously expressed protein, has classically been considered the main iron cellular storage molecule in the body. Owing to the ferroxidase activity of the H-subunit and the nucleation ability of the L-subunit, ferritin can store a large amount of iron within its mineral core. However, recent evidence has demonstrated a range of abilities of ferritin that extends well beyond the scope of iron storage. This review aims to discuss novel functions and biomedical uses of ferritin in the processes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 137 publications
(181 reference statements)
1
81
0
Order By: Relevance
“…The ferritin was genetically engineered by inserting nanobodies sequence at the C-terminus, thereby replacing the ε-helix of the P. furiosus ferritin subunit. Then, the ferritin fused nanobody (fenobody) can self-assemble into a nanocage and more nanobodies are displayed on the surface of nanocage [24,44]. Then, the fenobody showed higher affinity to antigen compared with the traditional nanobody.…”
Section: Discussionmentioning
confidence: 99%
“…The ferritin was genetically engineered by inserting nanobodies sequence at the C-terminus, thereby replacing the ε-helix of the P. furiosus ferritin subunit. Then, the ferritin fused nanobody (fenobody) can self-assemble into a nanocage and more nanobodies are displayed on the surface of nanocage [24,44]. Then, the fenobody showed higher affinity to antigen compared with the traditional nanobody.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin heavy chain protein has found many biological applications in nanomedicines and molecular diagnostics [15][16][17]. Lately, a few constructs based on ferritin have been developed as antivirus and anticancer vaccines [10,11,13].…”
Section: Construction Of Rbm-hftnmentioning
confidence: 99%
“…However, in addition to iron, ferritin has the unique ability to encapsulate and deliver other molecules. Many recent reviews have focused on various aspects of the use of this nanocage as a drug delivery system [9,10]. This review aims to discuss the peculiar role of an apoferritin cage not only for the specific delivery of MRI CAs but also to obtain significant relaxivity enhancement with consequent efficacy improvement.…”
Section: Introductionmentioning
confidence: 99%
“…These peptide chains are present in different ratios in various organs to form a cage architecture of 12 nm in external diameter with an interior cavity of 8 nm [11]. Although functions of ferritin are traditionally associated with intracellular iron storage, recent studies have demonstrated ferritin ability for iron delivery and transport [9]. In particular, studies have demonstrated H-ferritin-mediated iron delivery to the brain through the blood-brain barrier, demonstrating that H-ferritin can replace transferrin as an iron source for oligodendrocytes in vitro [12].…”
Section: Introductionmentioning
confidence: 99%